2022
DOI: 10.1007/s11103-022-01295-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of GmFAD3 expression alters abiotic stress responses in soybean

Abstract: Fatty acid desaturases (FADs) are a class of enzymes that mediate desaturation of fatty acids by introducing double bonds. They play an important role in modulating membrane uidity in response to various abiotic stresses. However, a comprehensive analysis of FAD3 in drought and salinity stress tolerance in soybean is lacking. We used Bean Pod Mottle Virus (BPMV)-based vector for achieving rapid and e cient overexpression as well as silencing of Omega-3 Fatty Acid Desaturase gene from Glycine max (GmFAD3) to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Fatty acids are critical components of the cell membrane and are affected by environmental stresses. However, fatty acid desaturases (FADs) are a class of enzymes that mediate desaturation of fatty acids by introducing double bonds, helping the cell membrane to retain its function under stress by producing unsaturated fatty acids [ 89 , 90 , 91 ]. They play a significant role in modulating membrane fluidity in response to various abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acids are critical components of the cell membrane and are affected by environmental stresses. However, fatty acid desaturases (FADs) are a class of enzymes that mediate desaturation of fatty acids by introducing double bonds, helping the cell membrane to retain its function under stress by producing unsaturated fatty acids [ 89 , 90 , 91 ]. They play a significant role in modulating membrane fluidity in response to various abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation revealed that plants with overexpression of FADs showed higher chlorophyll content, photosystem II efficiency, relative water content, transpiration rate, stomatal conductance, and proline content, as well as a cooler canopy under drought and salinity stress conditions. However, FAD -silenced soybean plants were more sensitive to drought and salinity stresses [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of GmWRK54 enhanced abiotic stress tolerance due to over accumulation of osmoprotectants and better cooling canopy. 53 GmWRK54 was also shown to induce stress tolerance by activation of abscisic acid and Ca + pathways. 58 …”
Section: Expression Of Fatty Acid Genes In Vegetative Tissues and The...mentioning
confidence: 99%
“…Fatty acid desaturases (FADs) cause the desaturation of fatty acids by introducing double bonds and modulates membrane fluidity in response to abiotic stresses. Similarly, the overexpression of the Omega-3 Fatty Acid Desaturase in soybean showed higher accumulation of JA levels, chlorophyll content, RWC, proline content and higher expression of GmWRKY54 as compared to GmFAD3 -silenced plants and exhibited drought and salt tolerance ( Singh et al., 2022 ). Similarly, overexpression of GmNAC109 , a homologous of AtAF1 in Arabidopsis, enhanced the drought and salt tolerance.…”
Section: Overexpression Of Soybean Salt-responsive Genesmentioning
confidence: 99%